Household Net Wealth: An International Comparison - Iris Claus; Grant Scobie (New Zealand Government, The Treasury, 2001)
Household saving can be measured as either the difference between the flows of current income and expenditure, or through households' balance sheets as changes in the stocks of accumulated net wealth. This paper examines household saving in New Zealand and other OECD countries, with particular focus on the stock of net wealth. The ratio of real assets to disposable income in New Zealand is close to OECD levels. However, household financial net wealth as a proportion of disposable income has been falling in New Zealand since the late 1980s, whereas it has been rising in other OECD countries. As a result, housing assets in New Zealand have become an increasing share of households' wealth portfolios. The implied savings rate from households' balance sheets is significantly higher than the flow measure. Moreover, it follows the business cycle more closely, consistent with consumption smoothing behaviour by households.
Keywords: E21; N20; 330; Household net wealth; saving; financial deregulation